Edyta Stein w polskiej historiografii - Vall, Katarzyna du (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Saint Teresa Benedicta of the Cross, also known as Edith Stein 1891–1942, was a German philosopher of Jewish descent and a Discalced Carmelite. Regarded as a martyr, she was canonized by the Catholic Church. The article is devoted to the interest of Polish researchers and of the Polish press in Edith Stein during the past six decades. Her life and philosophical thought became a subject of analysis soon after her death. Edith Stein had already been mentioned in Catholic press during the Stalin Era in the early 50s. In the 60s the number of articles about her doubled. The most indepth comment and the first translation of Stein’s work appeared in 1968 in spite of the anti-Semitic campaign in Poland. In the 70s the number of publications doubled once again. Some of her major works were translated into Polish and the first biography of Edith Stein was written. In the 80s over 100 publications came out, and in the 90s — another 250. Although many of works written by Edith Stein were translated into Polish, there is still much work to be done — in my opinion in the first place An Investigation Concerning the State should be published in Polish.
Keywords: Stein,Edith (1891-1942); polscy badacze; prasa polska